Influence of rubber nature on properties of dynamic thermoplastic elastomer - T. V. Konovalova; V. D. Yulovskaya; O. A. Serenko (Тонкие химические технологии, 2010)
The influence of the elastomer nature on the properties of mixtures and of dynamic thermoplastic elastomers based on polyethylene was analyzed. It was shown that the nature of rubber affects the character of deformation and mechanical properties of materials. The dynamic thermoplastic elastomers based on 1,2-polybutadiene retain their properties upon artificial ageing and are more stable than those based on ethylenepropylenedienic rubber (EPDM).